Teacher Perception toward Offline Final Examination on Covid-19 Pandemic - Rasyid Anwar Dalimunthe; Syaripuddin Daulay; Lusinta Rehna Ginting; Mely Nadia (STAI Hubbulwathan Duri, 2021)
The purpose of this study was to determine the implementation of the semester exams with an offline system. To get more accurate information about teachers' perceptions of the quality of student answers in the semester exams and student compliance with the rules of returning the questions promptly. The research method used is quantitative research methods with descriptive research design. The sample used in this study was 49 teachers who taught various subjects listed in the 2013 revised SMK level curriculum. While the data collection tools used were observation, questionnaires, interviews, literature study, then explained through tables and presented or tabulated by the teacher's answers using formulas. The results showed that the teacher's perception of students' answers in the offline system semester exams was poor or 63.26%. Meanwhile, students' compliance with the rules of returning the questions and answers showed that they were on time or 48.97%. So the researchers argue that the implementation of the semester exams with the offline system needs to be improved or look for other ways to improve the quality of student answers. And student compliance in returning questions and answers can be maintained and further enhanced for students who are still in the category of not being on time and not on time.